O contexto da inclusão nas produções de pós-graduação em educação das IES do Paraná de 2015 a 2022 - Morandi, Cassiana Patricia (2023)
This research was developed during the Master's program in the Stricto Sensu Postgraduate Program in Education, in the concentration area: Education, in the research line Culture, Educational Processes and Teacher Training, at the State University of Western Paraná– UNIOESTE. The main objective is to evaluate the context of inclusion as a school phenomenon, in the way it is presented in scientific productions, developed in stricto sensu courses in Education at State Institutions of Paraná (IES/PR), in the period from 2015 to 2022. We present a brief history and the legality of inclusive education, ensuring the right to education according to laws that treat inclusion as a fundamental right for all, advocating for everyone based on human rights. We address inclusive education in Brazil and Paraná,following this line of thought that seeks, through public policies, to include in basic education those with some type of special educational needs. This qualitative research employs bibliographic methodology. We sought frameworks in dissertations and theses completed from2015 to 2022, in the seven public state Higher Education Institutions in the State of Paraná that offer stricto sensu postgraduate courses in education. Of these, five have completed dissertations and theses: State University of Londrina - UEL, State University of Maringá - UEM; State University of Ponta Grossa - UEPG; State University of the Midwest - UNICENTRO; State University of Western Paraná - UNIOESTE. The results obtained allow usto affirm that inclusion is the subject of study in higher education institutions in Paraná, in acontext of discussion and reflection on how this inclusion is being implemented and how this challenge is being addressed in the educational environment.